Evaluation of orthosis rapid prototyping during the design process: Analysis of verification models - Ferrari, Ana Lya Moya [UNESP] (2020)
Physical prototypes allow the testing of ideas quickly with models that look similar to the final product. Rapid Prototyping (RP) based on additive or subtractive technologies allow trial usability tests to avoid errors and failures in the final product production. These technologies are increasingly used in orthosis production. Design processes involving RP can facilitate usability tests to asses comfort, safety, and performance of the orthoses. The objective of this study was to review the use of RP for orthoses prototype production for user evaluation. The results show that FDM was the most common technique. Half of the studies involved user’s participation or evaluation in the design processes, although, only three out of thirty-eight studies used RP in proof of concept production.